Hubungan Antara Kepuasan Pelanggan dan Konsep Diri Dengan Perilaku Konsumtif Dalam Melakukan Belanja Online Menggunakan E-Commerce Shopee Pada Mahasiswa Psikologi Di Universitas Tama Jagakarsa - Nanda Dwi Kholifah; Tjitjik Hamidah; Sri Cahya Kencana (PT. Hasba Edukasi Mandiri, 2025)
The purpose of this study is to determine the relationship between customer satisfaction and self-concept with consumptive behavior in online shopping using E-Commerce Shopee among Psychology students at Universitas Tama Jagakarsa. The measurement tools used include a consumptive behavior scale modified based on the indicators proposed by Sumartono (2023), a customer satisfaction scale modified based on aspects proposed by Kotler and Keller (in Sajidah, 2023), and a self-concept scale adapted from the Personal Self Concept (PSC) Questionnaire created by Goni (2011). The population of this study consists of 125 Psychology students at Universitas Tama Jagakarsa. The sample was selected using Total Sampling technique. The results of the multi-correlation coefficient analysis on customer satisfaction and self-concept with consumptive behavior obtained an R value of 0.415 and an R Square of 0.172. The Pearson product-moment correlation coefficient analysis revealed that the correlation between customer satisfaction and consumptive behavior was r = 0.340 with a Sig value of 0.001 (<0.05), and the correlation between self-concept and consumptive behavior was r = -0.217 with a Sig value of 0.034 (<0.05). It can be concluded that there is a significant relationship between customer satisfaction and self-concept with consumptive behavior. There is a positive relationship between customer satisfaction and consumptive behavior, and a negative relationship between self-concept and consumptive behavior.